Knowledge, attitude, and practice of psoriasis patients toward their diseases: a web-based, cross-sectional study - Tian, Jun; Zhang, Lei; Zhao, Xiangrong; Yang, Li (Frontiers in Medicine, 2024)
Objective To investigate the knowledge, attitude, and practice (KAP) of psoriasis patients toward the disease. Methods A web-based cross-sectional study was conducted among psoriasis patients who were diagnosed at the outpatient of Shaanxi Provincial People’s Hospital in March 2023. A self-designed questionnaire was administered for data collection and KAP assessment. Results A total of 526 valid questionnaires were included, including 257 males (48.86%) psoriasis patients. Their mean KAP scores were 8.09 ± 3.60 (possible range: 0–12), 31.94 ± 4.61 (possible range: 10–50), and 51.92 ± 8.83 (possible range: 15–75), respectively. Pearson’s correlation analysis showed a positive correlation between knowledge and attitude (r = 0.186, p < 0.001), a positive correlation between knowledge and practice (r = 0.313, p < 0.001), and a negative correlation between attitude and practice (r = −0.181, p < 0.001). Moreover, structural equation model showed that medication (β = 2.74, 95% CI: 2.17, 3.32, p < 0.001) has significantly positive effect on knowledge. Education (β = 0.56, 95% CI: 0.31, 0.81, p < 0.001) and duration of psoriasis (β = 1.01, 95% CI: 0.54, 1.49, p < 0.001) have significantly positive effect on attitude. Knowledge (β = 1.03, 95% CI: 0.80, 1.26, p < 0.001) and medication (β = 4.59, 95% CI: 2.78, 6.40, p < 0.001) has significantly positive effect on practice, while attitude (β = −0.41, 95% CI: −0.57, −0.26, p < 0.001) and duration of psoriasis (β = −2.53, 95% CI: −3.49, −1.57, p < 0.001) exhibit significantly negative effect on practice. Conclusion Psoriasis patients have good knowledge, positive attitude, and proactive practice toward the disease. Education, medication, duration of psoriasis might have effect on their KAP.